Using system dynamics to illustrate deming’s system of profound knowledge - Stepanovich, Paul L (Total Quality Management & Business Excellence, 2004)
This article presents a systems dynamics model to illustrate some of the aspects of Deming's System of Profound Knowledge. As a pedagogical tool, it would serve as a useful introduction for those new to Deming's ideas. It not only introduces the main parts of his system, but also highlights their interconnectedness. The model environment, an interactive management flight simulator, and the model content combine to provide several learning opportunities. The model uses the assumptions of regression to the mean, the 80:20 Rule, random walks, and learned helplessness to present a theory of how, managers learn to reduce quality in organizations. Those interested in exploring or teaching Deming's System can use the model as a launching point from which to explore the system further. Running the simulation provides an opportunity to identify and challenge assumptions, explore the harmful effects of tampering, examine the fundamental attribution error, develop control charts, and challenge the application of behaviourism in management.
8 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-680-699-761-383 tex.type: [object Object]
Keywords: Deming; Pedagogy; Quality; System dynamics; dept.mgt

Process mapping in successful ERP implementations - Okrent, Michael D; Vokurka, Robert J (Industrial Management and Data Systems, 2004)
This paper discusses the six core business processes and supporting technology that are impacted by an enterprise resource planning (ERP) implementation. It begins with a brief history of the evolution of ERP and the information systems technology that enabled its development. A discussion of project implementation team preparations is followed by a description of process mapping and its significance to the success of an ERP implementation. Highlights of “As-Is” and “To-Be” process mapping and change management conclude the paper. © 2004, Emerald Group Publishing Limited
69 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-734-989-711-339 tex.type: [object Object]
Keywords: Business processes; Costs; Enterprise resource planning; Information analysis; Information technology; Maintenance; Optimization; Planning tools; Process analysis; Process mapping; Resource management; Strategic planning; dept.mgt

Giving back: women's entrepreneurial philanthropy - Oppedisano, Jeannette (Women in Management Review, 2004)
Traditionally, the concept of entrepreneurship included a for-profit bottom line. Recently, however, researchers have begun to explore an adaptation of this model called “social entrepreneurship”; that is, creating organizations for the greater good of a community, region, nation, or the world. These entrepreneurs use money that they made or inherited to establish organizations from a missionary and visionary posture. This is an arena where women have had significant impact, yet little has been written to celebrate their contributions. The purpose of this paper is to explore the concept of such philanthropy, to suggest where this social ethic might have had its origins, and to provide samples of women who have been entrepreneurial in their social commitment. Suggestions for future research on women's entrepreneurial philanthropy will also be made. © 2004, Emerald Group Publishing Limited
9 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/020-771-605-085-74X tex.type: [object Object]
Keywords: Entrepreneurialism; Philanthropy; Social action; United States of America; Women; dept.mgt